2004
DOI: 10.1152/japplphysiol.01159.2002
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite does not impair pulmonary and systemic vascular responses

Abstract: The effects of peroxynitrite (ONOO-) on vascular responses were investigated in the systemic and hindquarters vascular bed and in the isolated perfused rat lung. Intravenous injections of ONOO- decreased systemic arterial pressure, and injections of ONOO- into the hindquarters decreased perfusion pressure in a dose-related manner. Injections of ONOO- into the lung perfusion circuit increased pulmonary arterial perfusion pressure. Responses to ONOO- were rapid in onset, short in duration, and repeatable without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 30 publications
5
23
3
Order By: Relevance
“…These data suggest that PN does not impair endothelial function in the hindlimb vascular bed. The results showing that vasodilator responses to acetylcholine are not inhibited are consistent with results in the hindquarters vascular bed or in aortic rings of the rat, in isolated cat coronary arteries, and in isolated rat pulmonary arteries where responses to acetylcholine were enhanced by the highest dose of PN studied [25,105,125,202]. These data are in contrast to studies showing that responses to vasodilator agents, including acetylcholine, are reduced after the development of tachyphylaxis to PN [59,154].…”
Section: Vasorelaxant Properties Of Peroxyni-tritesupporting
confidence: 82%
See 4 more Smart Citations
“…These data suggest that PN does not impair endothelial function in the hindlimb vascular bed. The results showing that vasodilator responses to acetylcholine are not inhibited are consistent with results in the hindquarters vascular bed or in aortic rings of the rat, in isolated cat coronary arteries, and in isolated rat pulmonary arteries where responses to acetylcholine were enhanced by the highest dose of PN studied [25,105,125,202]. These data are in contrast to studies showing that responses to vasodilator agents, including acetylcholine, are reduced after the development of tachyphylaxis to PN [59,154].…”
Section: Vasorelaxant Properties Of Peroxyni-tritesupporting
confidence: 82%
“…The hindlimb vasodilator responses to PN were rapid in onset, short in duration, and the vasodilator responses to PN could be repeated without causing tachyphylaxis [210]. The absence of the development of tachyphylaxis to the vasodilator response to PN is in agreement with studies in the systemic and hindlimb vascular bed of the rat, and in isolated coronary arteries from the dog and cat [23,25,202]. Although PN has been reported to produce vascular dysfunction, the results of these studies observed that vascular responses of PN to could be repeated as subsequent injections, in doses up to 4000 nmol, had no significant effect on baseline perfusion pressure or on responses to vasoactive agonists [210].…”
Section: Vasorelaxant Properties Of Peroxyni-tritesupporting
confidence: 81%
See 3 more Smart Citations